A coal‐based strategy to reduce Europe's dependence on Russian energy imports1. Issue 5 (October 2014) - Bezdek, Roger
Abstract Europe is dangerously dependent on Russian natural gas (NG): 13 European nations rely on Russian NG for over 50 % of their requirements. In addition, Europe relies on Russia for about one third of its oil imports. Europe is acutely aware of this high level of energy dependence, which has been, once again, highlighted by the Ukrainian crisis. The European Council March 2014 Brussels Summit Meeting focused on Europe's energy dependence on Russia, especially for NG. The Summit recommended that efforts be intensified to reduce Europe's gas energy dependency and that the EU accelerate diversification of its energy supply. However, via a carefully thought out strategy, Europe can significantly reduce its dependence on Russian energy supplies through greater utilization of clean coal.